The Relationship Between Gender And Student Stigmanization After The Covid-19 Out Break In The Campus Environment - Riawati, Danik; Rasmi , Rasmi (Health Frontiers: Multidisciplinary Journal for Health Professionals, 2024)
The Covid-19 outbreak that attacks society can be a bad experience that will last a lifetime.This gives fear and panic, as well as negative thoughts in all ages and genders, due to the large number of affected victims who die every day. Objective to determine the relationship between gender and the emergence of students' negative assumptions about the Covid-19 outbreak in the campus environment.. This type of research is analytical observational with a cross sectional research design.The population used was students of the Diploma Three in Blood Bank Technology class A study program, totaling 48 respondents. The research sample uses the entire population (saturated sampling). Data collection techniques use primary data in the form of closed questionnaires, univariate analysis in the form of frequency distribution tables, bivariate analysis with the Eta correlation test. Results: The number of respondents was 48 and the female gender dominated, namely 37 (77.1%) respondents and 11 (22.9%) male respondents. The stigmatization score was less strong with a score of 1-6, there were 34 respondents and there were 14 respondents with a strong stigmatization score of 7-10. Conclusion: Eta values are 0.237 and 0.203, meaning the degree of relationship between gender and stimanization is low.